Clínica de la enfermedad de Chagas - Pesce, Hugo (1954)
No object of this conference is one, albeit succinct, comprehensive exposition of the notions of Chagas disease. Only attempt has been made after some preliminary memories and then to highlight the epidemiological findings in the region of Arequipa, illustrate the clinical Chagas disease, especially in its acute phases and with particular reference to the integumentary syndromes; clinic wealth and variety, built by Mazza, which exceeded by far the current notions of ophthalmic-nodal complex and chronic myocarditis, which dominate the general treaties.